3-D Neutronics Assessment of Tritium Breeding Capacity and Shielding of Tokamak-Based Fusion Nuclear Science Facility. (3rd October 2017) - Harb, M.; El-Guebaly, L.; Davis, A.; Wilson, P.; Marriott, E.; Benzaquen, J.; ,
Abstract: Two issues related to neutronics analysis of fusion systems were addressed for the purpose of physical design iterations as well as plant operation: tritium self-sufficiency and shielding of the inboard magnet. State-of-the-art modeling/analysis tools facilitated a full 3-D neutronics analysis of the latest FESS-FNSF design. The first stage of the analysis involved the selection of materials for the first wall and blanket along with shielding materials to protect the magnet based on extensive 1-D analyses. The second stage is a stepwise workflow to estimate the overall tritium breeding ratio with high fidelity. It involved a bottom-up approach by coupling the CAD model with the 3-D MCNP code using DAGMC and adding the relevant design details in steps to assess the effect of such details on the tritium breeding ratio. The final stage involved calculations of the values of damage parameters at specific components: the first wall, the vacuum vessel, and magnet.